Рідкісні види афілофороїдних грибів з Національного природного парку "Гомільшанські ліси" (Харківська обл.) - Усіченко, А.С. (Український ботанічний журнал, 2011)
В результате исследований, проведенных в 1999—2009 гг. на территории НПП «Гомильшанские леса» (Змиевский р-н, Харьковская обл., Украина), выявлено 6 видов афиллофороидных грибов (Albatrellus cristatus, Hericium cirrhatum, Sarcodontia crocea, Skeletocutis odora, Spongipellis spumeus и Xylobolus frustulatus), требующих охраны. Осуществлена оценка их раритетности в соответствии с критериями МСОП и предложены мероприятия по их охране. As a result of surveys conducted in 1999—2009 in the Gomilshanski Lisy National Nature Park (Zmiyiv District, Kharkiv Region, Ukraine), 6 species of rare aphyllophoroid fungi were registered (Albatrellus cristatus, Hericium cirrhatum, Sarcodontia crocea, Skeletocutis odora, Spongipellis spumeus and Xylobolus frustulatus). The species were evaluated according to the IUCN criteria. Some measures for their conservation are proposed.